Simbolisme Tradisi Pecah Kuali di Dusun Watugandu Kabupaten Semarang - Bahri, Muchammad Syaiful; Anggraeni, Sri Prastiti Kusuma (Sutasoma : Jurnal Sastra Jawa, 2021)
Abstract The tradition of pecah kuali is a unique tradition, it means that this tradition only exists in Dusun Watugandu, Kec. Sumowono, Kab. Semarang. This pecah kuali tradition is still carried out today, but the traditional actors or the supporting community do not understand the symbolic form and meaning in the tradition of pecah kuali. The problems studied are: (1) what is the form of the tradition of pecah kuali in Dusun Watugandu, Kab. Semarang, (2) what is the symbolic meaning in the tradition of pecah kuali in Duwun Watugandu, Kab. Semarang. This research aims to describe form and meaning of the symbols in this tradition of pecah kuali. The theory used as the basis is the theory of symbols. So, the approach used is phenomenology approach. method through observation, interview, and documentation. Data analysis using content analysis techniques. Data collection techniques used are observation, interviews, and documentation. Data analysis using content analysis techniques. This study shows that the forms of the pecah kuali tradition is eclipse prayer, hiding, pecah kuali ritual, and pamongan, so the tradition of pecah kuali is partly verbal folklore. The symbolic meaning contained in the tradition of pecah kuali is found in the ubarampe used, namely the symbol of ease of delivery, refusal of balak, protection of the fetus, existence, closeness, democracy, and blessing. So the meaning of the symbols in this tradition of pecah kuali is a form of human relationship with God, with nature, and with each other. plea for salvation, forgiveness, and thanksgiving to Allah SWT for all blessings. The meaning of the symbols in this tradition of pecah kuali as a medium or intermediary in his religion, as well as to show the existence of his culture. Keywords: simbolism, tradition, tradition of pecah kuali